PERLINDUNGAN HUKUM MEREK TERKENAL TERHADAP PENGATURAN PRINSIP PERSAMAAN PADA POKOKNYA YANG DIAJUKAN DENGAN ITIKAD TIDAK BAIK (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR: 92K/PDT.SUS-HKI/2017) - Vira Adryani; Christine S.T. Kansil (Jurnal Hukum Adigama, 2020)
Often there are applicants who have bad intentions in registering their trademarks, especially those that have substantially or in full similarity with well-known marks. This can be detrimental to the party being imitated because it will affect the decline in profits and loss of brand reputation. If there is a party who feels that it has been harmed by the registration, they may file a lawsuit for the cancellation of the mark. The method used in this paper is a normative legal research method. The results showed that the application of the equation assessment criteria in essence can be proven in the Judgment on Cassation level No. 92K / Pdt.Sus-HKI / 2017 between the famous Hugo Boss brand and the disputed “Hugo” brands. The application of the law by the Panel of Judges was correct because it had been proven that the “Hugo” brands owned by Teddy Tan had bad faith in registering their trademarks which were basically similar to the well-known brand, namely Hugo Boss. Moreover, Hugo Boss has already been registered and the famous brand should have received legal protection that has been guaranteed by the state as a consequence of the exclusive rights attached to the brand. Registration with an element of bad faith with equality assessment indicators will basically be rejected by the Directorate General of IPR based on Article 21 paragraph (1) and paragraph (3) of Law No.20 of 2016 concerning Trademarks and Geographical Indications because it can be misleading and cause confusion in Public.